2004
DOI: 10.1126/science.1096647
|View full text |Cite
|
Sign up to set email alerts
|

h/e Magnetic Flux Modulation of the Energy Gap in Nanotube Quantum Dots

Abstract: We report experiments on quantum dot single-electron-tunneling (SET) transistors made from short multiwall nanotubes and threaded by magnetic flux. Such systems allow us to probe the electronic energy spectrum of the nanotube and its dependence on the magnetic field. Evidence is provided for the interconversion between gapped (semiconducting) and ungapped (metallic) states. Our tubes exhibit h/e-period magnetic flux dependence, in agreement with simple tight-binding calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
103
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(105 citation statements)
references
References 24 publications
(47 reference statements)
2
103
0
Order By: Relevance
“…Since the chirality enters the problem as a fictitious flux, the physical properties of graphene tubes can be dramatically affected by the presence of an axial magnetic field as was anticipated theoretically [7,11,12] and observed experimentally [13]. Indeed, imagine there is an axial Aharonov-Bohm (AB) flux Φ [14] entirely confined within the interior of the cylinder.…”
Section: Effects Of An Axial Magnetic Fieldmentioning
confidence: 92%
See 1 more Smart Citation
“…Since the chirality enters the problem as a fictitious flux, the physical properties of graphene tubes can be dramatically affected by the presence of an axial magnetic field as was anticipated theoretically [7,11,12] and observed experimentally [13]. Indeed, imagine there is an axial Aharonov-Bohm (AB) flux Φ [14] entirely confined within the interior of the cylinder.…”
Section: Effects Of An Axial Magnetic Fieldmentioning
confidence: 92%
“…First we note that there is a series of conductance measurements [13,[15][16][17] and an expertise on how to deal with the end effects is growing. For example, Javey et al [17] found that the resistance of a nanotube was rather close to the expected 6.5 kΩ; they estimated that the leads and contacts contributed no more than 0.6 kΩ (and much less at low temperatures).…”
Section: Effects Of Finite Lengthmentioning
confidence: 99%
“…[19][20][21][22][23][24][25] Further theoretical studies [26][27][28][29] reveal that the transport properties are directly related to the magnetic-field modulated density of states. The SOI-modified band structure and its implications on the electronic properties of CNT's in a magnetic field have been in the focus of extensive theoretical work.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in hole-or electron doped nanotubes the behaviour of µ orb (φ) depends strongly on the chirality of the nanotube, on its size, and on the degree of hole or electron doping. In our model calculations we study nanotubes in the ballistic regime and we work in the non-interacting electrons approximation which has yielded good agreement with experimental results in mesoscopic rings [7] and in carbon nanotubes [3,8,9].…”
Section: Introductionmentioning
confidence: 52%